(SAPAXROLA XRY APKU]SRYs - (SSga(Suga(Svmfyga(Sw Df}ugc(Slrw Ms (University Studio Press, 2008)
(SAPAXROLA MYXXAUR RVXFRNRDLA APASPFYVXLMR VYVXJOA MYMNRZRULMR DFPPJXLMR VYVXJOA ALVKJXJULA RUDAPA SFSXLMR VYVXJOA PFYULMR VYVXJOA OYRNRDLAs
(SAPAXROLA MYXXAUR RVXFRNRDLA APASPFYVXLMR VYVXJOA MYMNRZRULMR DFPPJXLMR VYVXJOA ALVKJXJULA RUDAPA SFSXLMR VYVXJOA PFYULMR VYVXJOA OYRNRDLAs